Price Sensitivity and Information Barriers to the Take-up of Naloxone - Jacobson, Mireille,Powell, David (National Bureau of Economic Research, 2024)
We conducted a field experiment that randomized advertisements, advertisement content, and prices across 2,204 counties in the United States to study the impacts on online purchases of naloxone, an opioid overdose reversal drug. Advertising increased website users but only impacted purchases when combined with a price reduction. Messages emphasizing the discreet nature of online sales had no additional impact on purchases. Comparing counties with advertisements featuring a highly discounted price to those featuring the full price, we estimate a price elasticity of demand for online naloxone of -1.3. Price is a significant barrier to online purchases of this life-saving medication
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Droge; Drogenkonsum; Arzneimittel; Konsumentenverhalten; Preiselastizität; Feldforschung; USA; Health Behavior; Government Policy; Regulation; Public Health; Advertising